DISTRIBUSI DAN KEMELIMPAHAN FITOPLANKTON DI RAWA BIRU, MERAUKE - , LANGGA SWARAS FAHAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Rawa Biru is an amphibius ecosystem, in dry season this lake acted as shallow lake and midstream in rainy season. Distribution and abundance of phytoplankton influenced by environmental factor. The objective of this research were studied distribution and abundance of phytoplankton in Rawa Biru and the its regulation factor. The samples phytoplankton were collected seasonly, dry season 2011 and rainy season 2012. The samples were collected at three sampling stations, Tempe water coloum, and canal in dry and rainy. In water storage collected only in rainy season. In each sampling stations, water samples were collected with modification of Van dorn water sampler 5 L. Phytoplankton samples were collected 100 liter for it with 5 replicated each station. The dominant functional group were unicellular algae. The dominant species were Staurastrum sp. 5295 ind. per 100 liter in Tempeâs surface, 5057 ind. per 100 liter in Tempeâs sub surface, and 645 ind. per 100 liter in canal at dry season. At rainy season 437 ind. per 100 liter in Tempeâs surface, 426 ind. per 100 liter in Tempeâs sub surface, and 3319 ind. per 100 liter in canal This species are desmids unicellular algae. Abundance of the desmids is a indicator good water quality. Nutrient in Rawa Biru similar each season, phytoplankton growth is continous. Distribution and abundance phytoplankton in Rawa Biru regullated by predator-prey interaction (top-down).